Measuring the Corporate Entrepreneurship in the Hotel sector in Djerba island (Tunisia) during a critical period - HADJ HASSINE, Abir (Revue Internationale des Sciences de Gestion, 2025)
This paper investigates the concept of Corporate Entrepreneurship (CE) in the Tunisian hotel sector, focusing on Djerba Island during a critical period marked by the 2015 terrorist attacks that severely impacted tourism. The study relies on Zahra’s (1996) conceptual framework, defining CE as a multidimensional construct encompassing Innovation, Corporate Venturing, and Strategic Renewal. An empirical survey was conducted among managers and department heads of 26 operational hotels in Djerba, totaling 158 respondents. Data were analysed using exploratory and confirmatory factor analyses to assess the validity and multidimensionality of CE in this context. Results indicate that CE is a measurable multidimensional construct, with process innovation being the most emphasized dimension, followed by product and organizational innovation, corporate venturing initiatives, and strategic renewal. This research contributes to the literature by providing empirical evidence of CE during a crisis in the hotel sector and offers practical insights for management and decision-making.